Cost effectiveness of human papilloma virus vaccination in low and middle income countries: a systematic review of literature. (2nd January 2018) - Silas, Olugbenga Akindele; Achenbach, Chad J.; Murphy, Robert Leo; Hou, Lifang; Sagay, Solomon Atiene; Banwat, Edmund; Adoga, Adeyi A.; Musa, Jonah; French, Dustin Douglas
ABSTRACT: Introduction : Low and middle income countries (LMICs) bear more than 50% of the current cervical cancer burden over the last decade with linkages to lack of HPV vaccination, high levels of poverty, illiteracy and nonexistent or poor screening programs. Governments of LMICs need enough convincing evidence that HPV vaccination will be more cost-effective in reducing the scourge of cervical cancer. Area covered : A systematic review to identify suitable studies from MEDLINE(via PubMed), EMBASE and Electronic search through GOOGLE for original and review articles from 2007 to 2014 on cost-effectiveness of human papilloma virus vaccination of pre-adolescent girls in LMICs was conducted. A total of 19 full articles were finally selected and reviewed after screening out those not consistent with the inclusion and exclusion criteria. Expert commentary : Most studies on cost-effectiveness of HPV vaccine in LMICs show that lowering cost of HPV vaccination with or without Pap smear screening is cost-effective in areas with high incidence of cervical cancer.